Transportation Service Application Program at PT Y - Faisal Umam, Aldo (Politeknik Siber Cerdika Internasional, 2021)
Many companies today realize that they need fast, accurate and timely information to make decisions, the administrative activities of the organization will affect whether or not the decisions taken by the company. Delays in organizational activities will also affect decisions, where decisions are required accuracy and speed. The research was conducted at CV Amarta Nawa Indonesia in Jakarta research method using qualitative deriktif. Data obtained from interview data sources obtained from documents and informants. Research informants are managers, staff and primary documents from CV Amarta Nawa Indonesia in Jakarta. Data analysis is carried out with interactive technical analysis, which includes data collection, data presentation, data reduction and conclusion drawing. The creation of The Transportation Service Application Program aims in addition to making it easier for employees to also be able tofesiensi time, both in the process of inputting, searching and processing monthly data. With this application program, employees can reduce the level of errors and errors in the delivery of job order data and car orders